Midiatização presidencial: uma análise das estratégias enunciativas do último debate televisivo das eleições de 2022 - Eckhardt, Andreia Primaz (2025)
This study aims to analyze the enunciative strategies employed by the two candidates for the presidency of Brazil, Lula and Bolsonaro, during the final televised debate of the second round of the 2022 presidential elections. The debate took place at Estúdios Globo and was broadcasted by G1, TV Globo, GloboNews, and Globoplay on October 28, starting at 9:50 PM, lasting two hours, and moderated by the journalist William Bonner. Taking into account the theses proposed in this research — which investigates how, in a politically polarized context in Brazil, the candidates used enunciative strategies in this debate — we explore the concepts of political polarization, presidential mediatization, and televised debates. Initially, to reflect on the political and social context, we draw on the works of Borges and Vidigal (2018), Alkimin and Terron (2022), as well as Lögfren, Sartoretto, and Rosa (2023). To further examinate the concept of polarization, we rely on Braga (2020). Regarding mediatization, we reference the theoretical contributions of Hepp and Couldry (2020), Martino (2018), Verón (2004), Fernández (2018; 2021), and Carlón (2018). To specifically address presidential mediatization and/or electoral processes, we incorporate the works of Mangieri (2012), Ossa (2012), Abélés (2012), Soto (2012), Ollivier (2012), Cingolani (2014), Baptista (2023), and Lögfren, Sartoretto, and Rosa (2023). Our empirical object, the final televised debate, prompts us to better understand this format. To do so, we draw on the contributions of Vasconcellos (2011), Fausto Neto (2003), Fausto Neto and Verón (2003), and Rubim (2003). Methodologically, we adopt the evidential paradigm (Ginzburg, 1990), as problematized by Braga (2008) from a communicational perspective, and combine this approach with Verón’s sociosemiotics (1996; 2004; 2013) and Sodré’s (2006) concept of sensitive strategies. Through the theoretical framework of this dissertation and a close analysis of our empirical object, we identify four enunciative strategies: confrontation, self-promotion, emotion, and irony. Overall, we observe that both candidates employ these strategies throughout the debate. However, two stand out: confrontation and self-promotion. Nevertheless, all four enunciative strategies intertwine, highlighting the complexity of mediatization processes when analyzing fragments of the social fabric from a communicational perspective.